Learning Model Based on Perspective’s Student - Leni Mardiah NPT; Ulfa Lifia Bahri; Deasy Yunita Siregar (Pusat Riset dan Inovasi Nasional, 2024)
English is a language used for verbal and written communication. A mastery of communication is being able to decipher meaning from data, ideas, and feelings and use language to progress domains such as science, technology, and culture. English language competency is necessary to stay current with changes around the world. This study looked at how various teaching strategies and classroom setups affect students' interest in exploring art and culture. The results show that when the right techniques are used, excellent facilities increase students' motivation and facilitate easier and more effective learning. Furthermore, the provision of high-quality learning environments and the effective use of instructional strategies can support and enhance students' motivation to study.